High comprehensive complication index after minimally invasive esophagectomy associated with poor short-term and long-term outcome: a propensity score matching analysis - Wang, Xiaoqing; Yu, Jingchuan; Xie, Shuhan; Lin, Ye; Zhang, Peipei; Gao, Lei; Hong, Zhinuan; Kang, Mingqiang (Frontiers in Oncology, 2025)
IntroductionThe comprehensive complication index (CCI) is a valuable index to comprehensively and systematically evaluate complication severity. This study aimed to evaluate the predictive ability of comprehensive complication index on short- and long-term overall survival(OS) in patients with esophageal squamous cell carcinoma (ESCC) undergoing Mckeown minimally invasive esophagectomy (MIE).MethodsA total of 320 patients treated with radical MIE from 2013 to 2017 were included, and the primary outcome was OS. Firstly, the optimal cut-off value of CCI was determined by X-tile. Propensity score matching(PSM) was used to balance the baseline characteristics. Second, postoperative hospital stay and hospital costs between high- and low-CCI groups were compared. Third, the Kaplan-Meier survival curve was used to analyze survival differences. Fourth, Cox analysis was used to explore the risk factors of OS. Fifth, univariate and multivariate logistic analysis was used to determine the risk factors of high CCI.ResultsThe patients with CCI > 24.2 was defined as high-CCI group, and those with CCI ≤ 24.2 were assigned to low-CCI group. The high-CCI group had more hospital costs and longer hospital stays than the low-CCI group before and after PSM (both p<0.001). The Kaplan-Meier survival curve indicated that high-CCI group had worse prognosis both before and after PSM (before matching: P<0.001; after matching: P = 0.01). CCI was determined as an independent prognostic factor (before PSM, P = 0.001; after PSM, P = 0.003).ConclusionThe CCI could quantify postoperative complications after esophagectomy. High CCI was associated with longer postoperative hospital stays and expenses and is an independent risk factor for poor OS, holding great vlaue for reference for medical insurance, surgical quality and prognosis management.